8 Ossification of atherosclerotic plaque: the role of vessel derived stem cells. Issue 20 (23rd September 2011) - Leszczynska, A; O'Doherty, A; Barry, F; O'Brien, T; Murphy, M
Abstract : Introduction: Pericytes, although traditionally considered as supporting cells, have recently been proposed to have a more active role in the repair and pathogenesis of various vascular diseases. In this study, we hypothesised that a pericyte-like stem cell population, termed vessel derived stem cells (VSCs), with chondrogenic and osteogenic potential exists in the vessel wall and in the presence of the inflammatory cytokines seen in atherosclerotic environment contributes, along with the circulating mesenchymal stem cells, to the calcification of atherosclerotic plaque which occurs through the endochondral pathway. Methods: VSCs from aortae of ApoE−/− mice and control C57BL/6 mice were isolated and characterised for cell surface markers by flow cytometry and immunocytochemistry. MSCs from the bone marrow of these mice were also isolated and characterised. Chondrogenic potential of these cells was investigated in presence or absence of inflammatory cytokines such as IL-6 and IFN-γ. Results and Discussion: Isolated VSCs were strongly positive for Sca-1, CD44 and negative for CD31 and CD34. A sub-population of VSCs also expressed 3G5, a specific pericyte marker. Differentiation assays demonstrated the ability of the cells to undergo osteogenesis and chondrogenesis. VSCs had significantly higher GAG/DNA ratio than MSCs indicating comparatively increased chondrogenesis. That both MSCs and VSCs from the ApoE−/− atherosclerotic mice generate a more mature hypertrophic chondrocyte than cells from the C57BL/6 mice is interesting and suggests that the atherosclerotic environment may modulate the stem cell phenotype. Collagen-type II and aggrecan expression and effect of oxidised LDL on these cells in vitro will be investigated to further test this hypothesis.